(untitled) (International Journal of Economics Management and Social Science, 2026)
This article examines how Instagram advertising and structured content management shape brand visibility, customer engagement, and community relations for STJ Fresh Healthy, a Bandung-based micro, small, and medium enterprise (MSME) in the healthy beverage sector. Using a qualitative case study enriched with basic performance metrics (reach, impressions, interactions, follower growth), the study interprets Instagram as both a marketing tool and a social space where health-oriented lifestyles, trust, and local economic resilience are negotiated. The campaign design drew on a customer journey logic (awareness–consideration–action–post-purchase care) and focused on two promoted Reels: product introduction and production process. Results show substantial increases in reach (12,428 accounts), impressions (15,542 views), total interactions (95 for ads; 333 on feed; 169 on Reels), and follower growth (9% over two months), indicating that paid promotion can amplify MSME visibility and stimulate engagement. These outcomes resonate with broader evidence that Instagram marketing and sponsored content significantly support MSME brand development, customer-based brand equity, and performance when combined with creative visuals, interactive features, and consistent posting. Keywords : Instagram Ads, Community Engagement, MSME